THE EFFECT OF USING CARD-BASED MEMORY GAMES ON VOCABULARY MASTERY OF THE SEVENTH GRADE STUDENTS AT SMP NEGERI 8 PEMATANG SIANTAR - Agustina, Aulia; Manihuruk, Leonita Maria Efipanias; Situmeang, Siska (Dharmas Education Journal (DE_Journal), 2024)
The aim of this research is to determine the significant impact of memory games using modified cue cards on seventh grade students' vocabulary mastery at SMP Negeri 8 Pematangsiantar in the 2024/2025 academic year. This study specifically focuses on noun mastery. This research involved a population of 320 seventh grade students, who were then selected in two classes using purposive sampling techniques. The sample consisted of an experimental class (VII-1) with 32 students involved in memory games, and a control class (VII-2) with 32 students who received traditional instruction through teacher explanations. Data collection was carried out through multiple choice pre-test and post-test. The results showed that the average score of the experimental class increased from 47.9 in the pre-test to 74.5 in the post-test. In contrast, the average score of the control class increased from 55.6 in the pre-test to 65.3 in the post-test. The analysis shows a t-test value of 4.828 with degrees of freedom calculated as (n1 + n2 - 2), resulting in a total of 62. The critical t-value at the 0.05 significance level is 1.670. Because the observed t-test value (4.828) exceeds the critical t-value (1.670), the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. These findings indicate that there is a significant influence on students' vocabulary mastery when taught using memory games with cards at SMP Negeri 8 Pematangsiantar.